PERAN KOMUNIKASI ORANG TUA DAN ANAK DALAM MENUNJANG KEBERHASILAN BELAJAR SISWA KELAS II SDN 1 TEPUNG SARI - Yulaeha, Wiwin; Kuswidyanarko, Arif; Riyanti, Henni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the contribution of parent-child communication patterns to supporting the learning success of second-grade students at SDN 1 Tepung Sari. In early elementary school, children require intensive support, with family communication serving as the primary bridge for motivation and academic guidance. The research employed a descriptive qualitative method, with data collection techniques including in-depth interviews with parents and homeroom teachers, as well as documentation of student learning outcomes. The results indicate that two-way, open, and emotionally supportive dialogic communication significantly correlates with high student learning motivation and academic grades. Conversely, authoritarian communication patterns or minimal interaction tend to hinder children's confidence in learning. The main barriers identified include parents' limited time due to work commitments and a lack of understanding of how to effectively support their children in learning.